The value of feminism and the role of women in the 4.0 revolution era: Studying the book of Al-Mar'ah Al-Sholihah - Fuadi, Moh Ashif (Universitas Islam Negeri Ar-Raniry, 2021)
The discourse of feminism in the perspective of the pesantren kiai invites attention to be studied. Feminism is a movement that arises due to the arbitrary treatment of women who further demands equal rights and proper behavior between men and women. It’s just that, in its practice, there is a conventional way of thinking, and civilized has placed women not worth and even under men. This kind of culture has given birth to many problems and suffering in women because women are discriminated against, even receiving a lot of unfair treatment. Therefore, the feminist movement is trying to fight for women to get an equal and fair position in this era. This paper discusses the equality of rights between women and men in the book al-Mar’a al-Sholihah by Kiai Masruhan Maghfuri, who comes from pesantren. He is a scholar of Nusantara who discusses the praiseworthy morals for the generation of Muslim women. This research is classified as library research using a qualitative approach. The study results show that the study of feminism in the book and its relevance in its role in the era of revolution 4.0. Women have the right to get a balanced job and education with men to be good women for their country and change the economic sector by becoming a career women after carrying out their obligations to take care of the household. Women are given space to actualize themselves in the community without forgetting their nature.